The last 22 years of student lending – Analysis of the socio-economic impact of the student loan product family - Duráczky, Bálint (Public Finance Quarterly, 2023)
The Student Loan Center was established 22 years ago by the first civic government with the aim of increasing access to higher education. The measure was particularly important in channeling talented students from poor financial circumstances into higher education. Over the past two decades, both higher education and the socio-economic environment surrounding higher education have changed considerably. The aim of this study is to examine the extent to which student loan instruments have been able to maintain their effectiveness over this period. Through a historical overview and the presentation of results from questionnaire data collection, the study demonstrates that student loan products have adapted to the changing environment by introducing and adapting existing products, and that they are still very popular among higher education students.